EFFECTS OF CORPORATE INCOME AND VALUE ADDED TAX INCENTIVES ON THE PERFORMANCE OF EXPORT PROCESSING ZONE (EPZ) FIRMS IN KENYA - Kuria, Dr. John (European Journal of Business and Strategic Management, 2017)
With increased globalized economies characterized by stiff competition, there is a need for competitive tax systems, a strategy aimed at establishment of industries including EPZ so as to establish trading advantage. EPZs experience poor financial performance. There has been a decreasing trend in the number of employees recruited by EPZ firms in Kenya. The purpose of this paper was to establish the effect of corporate income tax incentive and VAT incentive on the performance of EPZ firms in Kenya. The study adopted a descriptive and explanatory research design. The study used a stratified sampling approach because the number of the EPZ firms in Kenya was categorized into 4 strata. The total numbers of firms used in the study were 86 registered EPZ firms in Kenya according to Export Processing Zones Authority (EPZA). The study adopted a census survey design. Primary data was obtained using questionnaires. Secondary data from the registered firms was collected on; ROA, total number of jobs created and the length of stay of the firms. The study used both descriptive and inferential statistics to conduct data analysis. The results of bivariate regression models adopted revealed that at 5% significance level corporate income tax incentive and VAT incentives had a positive and significant relationship with performance of EPZ firms measured using ROA and the total number of jobs. Based on the findings the study concluded that the government should continue to offer tax exemptions for it to attract and maintain foreign investors in the country. This study recommends that stakeholders in tax policy should reconsider the economic value of corporate tax incentive. Further, it was recommended that the government should reconsider its VAT policy by encouraging more VAT rebates to firms in order to boost their productivity and increase the volume of exports. Keywords: Corporate tax incentives, VAT incentive, performance, EPZ firms, ROA, number of jobs created and length of stay.